Marketing Mix and Relationship Marketing on Customer Loyalty with Customer Satisfaction as a Mediation Variable at BPRS Botani Bina Rahmah Bogor - Putra, Abdillah Jetha; Pertiwi, Tri Kartika; Ichsanuddin, Dhani (PT. Maju Malaqbi Makkarana, 2025)
Customer loyalty is an important aspect in maintaining the sustainability of BPRS amidst the increasingly tight competition in the Islamic financial industry. The objectives of this study are to analyze: (1) the influence of the marketing mix on customer loyalty, (2) the influence of relationship marketing on customer loyalty, (3) customer satisfaction mediates the influence of the marketing mix on customer loyalty, and (4) customer satisfaction mediates the influence of relationship marketing on customer loyalty. The sample of this study was 130 (one hundred and thirty) active customers of BPRS Botani Bina Rahmah Bogor, selected through a purposive sampling method with the criteria of having been a customer for at least six months. Primary data was collected through questionnaires, while analysis was conducted using the Partial Least Square (PLS) method with SmartPLS software version 4.0. The results of the study concluded that: (1) the marketing mix does not have a significant effect on customer loyalty, (2) relationship marketing has a significant positive effect on customer loyalty, (3) customer satisfaction is proven to mediate the effect of the marketing mix on customer loyalty, and (4) customer satisfaction also mediates the effect of relationship marketing on customer loyalty.